2017
DOI: 10.1021/acs.jpcc.7b03219
|View full text |Cite
|
Sign up to set email alerts
|

Site Dependent Atom Type ReaxFF for the Proton-Catalyzed Twin Polymerization

Abstract: ReaxFF is an efficient member of reactive molecular dynamics approaches to model chemical reactions for different chemical environments. Here it is applied to the structure formation process of twin polymerization, a newly developed method to obtain nanostructured functional materials. To achieve this, a site dependent atom type (SDAT) generalization of the classical ReaxFF approach is presented, which employs more then one atom type per chemical element. The efficacy of this SDAT-ReaxFF approach is demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…Atomistic simulations provide fundamental mechanistic insights into reactive processes and their consequences in polymeric materials that are difficult to elucidate from experiments alone. ,, Reactive force fields used with classical all-atom molecular dynamics (MD) are capable of reaching large time and space scales but frequently are not transferable to regions of chemical phase space beyond their fitting regime without extensive tuning. In contrast, quantum-based molecular dynamics (QMD) provides an accurate and transferable approach to predict condensed-phase chemistry. However, the extreme computational expense of QMD simulations with ab initio methods such as density functional theory (DFT) places significant limitations on the accessible time and length scales that can be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Atomistic simulations provide fundamental mechanistic insights into reactive processes and their consequences in polymeric materials that are difficult to elucidate from experiments alone. ,, Reactive force fields used with classical all-atom molecular dynamics (MD) are capable of reaching large time and space scales but frequently are not transferable to regions of chemical phase space beyond their fitting regime without extensive tuning. In contrast, quantum-based molecular dynamics (QMD) provides an accurate and transferable approach to predict condensed-phase chemistry. However, the extreme computational expense of QMD simulations with ab initio methods such as density functional theory (DFT) places significant limitations on the accessible time and length scales that can be studied.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 3 1 twin polymerizes to a phenolic resin ( 2 ) and silica network ( 3 ). From experimental [6,7,8,10,29,30] and theoretical [8,14,15,16,17,18] investigations it is known, that the acid catalyzed reaction mechanism is a reaction in a melt [8]. It can be characterized by three main reaction steps.…”
Section: Numerical Model Materials and Methodsmentioning
confidence: 99%
“…First, the methylene bonds open (ring opening process), second, the organic network formation via organic bond formations starts, and third, somehow later the inorganic network formation starts by opening the aryl bonds and forming the siloxane bonds at the same time. For further details to the reaction mechanism we refer the reader to [17,18,19].…”
Section: Numerical Model Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of detailed computational studies on the mechanisms of the TP process was reported. [16,[74][75][76][77][78][79] For example, a scale bridging approach was presented to simulate 2,2'spirobi[benzo-4H-1,3,2-dioxasiline] TP at the DFT level of theory giving insight into the structure as well as the reactivity at the molecular level. [16] This was later extended to include the influence of the counter anion of the used trifluoroacetic acid.…”
Section: Hybrid Materials Formation and Mechanismsmentioning
confidence: 99%